Geodetic GPS-based analysis of recent crustal motions in Victoria Land (Antarctica) - ZANUTTA, ANTONIO; VITTUARI, LUCA; GANDOLFI, STEFANO (Global and Planetary Change, 2008)
GPS measurements were collected within the framework of the VLNDEF (Victoria Land Network for DEFormation control) project, which was started in 1999 with the aim of detecting crustal deformation in Northern Victoria Land (Antarctica). The network was established in 1999 and is composed of one permanent station (TNB1), which has been observing since 1998, and 28 periodically surveyed control points. Three complete campaigns and some partial surveying of the network have been carried out to date. Data processing and analysis have been performed using an undifferenced approach for the network position within the ITRF. A doubledifferences- based strategy has been applied for movement detection. The data processing and analysis of results have been carried out for all available data, both periodically acquired and long time series. GPS measurements collected between December 1999 and February 2006 indicate a mean “absolute” motion of the region of ve=11.3 mm/yr and vn=−11.1 mm/yr and rock uplift rates of vu=2.8 mm/yr. These values are consistent with Antarctic plate motion and the general postglacial rebound models of the region. The relative motions within VLNDEF are small and only few points show velocities greater than the confidence levels.